Roles of Brassinosteroids and Related mRNAs in Pea Seed Growth and Germination - Nomura, Takahito; Ueno, Masaaki; Yamada, Yumiko; Takatsuto, Suguru; Takeuchi, Yasutomo; Yokota, Takao (Plant physiology (Bethesda), 2007)
The levels of endogenous brassinosteroids (BRs) and the expression of the biosynthesis/metabolism/perception genes involved have been investigated during the development and germination of pea (Pisum sativum) seeds. When seeds were rapidly growing, the level of biologically active BRs (brassinolide [BL] and castasterone [CS]) and the transcript levels of two BR C-6 oxidases (CYP85A1 and CYP85A6) reached a maximum, suggesting the significance of BL and CS in seed development. In the early stages of germination, CS, but not BL, appeared and its level increased in the growing tissues in which the transcript level of CYP85A1 and CYP85A6 was high, suggesting the significance of CS in seed germination and early seedling growth of pea. 6-Deoxocathasterone (6-deoxoCT) was the quantitatively major BR in mature seeds. At the early stage of germination, the level of 6-deoxoCT was specifically decreased, whereas the levels of downstream intermediates were increased. It seems that 6-deoxoCT is the major storage BR and is utilized during germination and early growth stages. The level of the mRNAs of BR biosynthesis and perception genes fluctuated during seed development. In mature seeds, most of mRNAs were present, but the level was generally lower compared with immature seeds. However, CYP90A9 mRNA rapidly increased during seed development and reached the maximum in mature seeds. The mRNAs stored in mature pea seeds seem to be utilized when seeds germinate. However, it was found that de novo transcription of mRNAs also starts as early as during seed imbibition.